(untitled) (CIPEEX, 2025)
This study examines whether jealousy, taken in isolation, amounts to a base motive for qualifying homicide and aggravating punishment under Brazilian criminal law. It is a doctrinal and case-law review that systematizes scholarship and judicial decisions to set criteria for identifying base motive and its effects on sentencing. The aim is to distinguish when jealousy is a mere passion-driven impetus—devoid of ignominy—and when, combined with elements such as possessiveness and control, disproportionate reaction, humiliation of the victim, or an abject purpose, it qualifies as a base motive. The method consisted of surveying treatises and appellate rulings, analyzing the factual-psychological context, the offender’s subjective elements, and the proportionality between motive and conduct. The findings indicate that jealousy alone does not meet the blameworthiness threshold required to recognize a base motive; robust proof and reasoned judicial explanation are required to show vileness, cruelty, or inhumanity as the crime’s determining reason. The conclusion is that the base-motive qualifier should be applied restrictively and with proper justification, avoiding undue aggravation and preserving typological coherence and substantive justice.